Neuronal cell‐type specific DNA methylation patterns of the Cacna1c gene. Issue Volume 31:Issue2(2013:Apr.) (23rd November 2012) - Nishioka, Masaki; Shimada, Takafumi; Bundo, Miki; Ukai, Wataru; Hashimoto, Eri; Saito, Toshikazu; Kano, Yukiko; Sasaki, Tsukasa; Kasai, Kiyoto; Kato, Tadafumi; Iwamoto, Kazuya
Abstract: Gene expression of the alpha‐1 subunit of the L‐type voltage‐gated calcium channel, CACNA1C, is known to be complexly regulated. Because CACNA1C is not only a crucial gene in normal brain function but also a promising candidate risk gene for psychiatric disorders such as bipolar disorder and schizophrenia, elucidating the molecular basis of transcriptional regulatory mechanism will be critically important. Here we examined DNA methylation status of CpG islands and a CpG island shore on mouse Cacna1c in neuronal and non‐neuronal nuclei, which were separated with a fluorescent activated cell sorting technique. We found that neurons and non‐neurons showed differential DNA methylation profile on a CpG island shore. This difference was evolutionarily conserved in human neuronal and non‐neuronal nuclei in the prefrontal cortex, suggesting that DNA methylation status on the CpG island shore of Cacna1c may have an important role in transcript regulation.